(untitled) (Bangladesh Journal of Medical Science, 2020)
Background: 80% of people with a stroke have impairment of the upper limb (UL). The hemiparetic arm is one of the most devastating consequences after stroke. Improving use of the affected UL is important however, because difficulty in using this UL in daily tasks has been related to lower quality of life. Design: A prospective randomized control trial type study. Setting: Malaysia Government and Private Hospitals and also in private Physiotherapy Centre’s. Population: A total of 25 subjects post stroke were randomly assigned to either in experimental group (n=13) and control group (n=12). Methods: Control group received 45 minutes of treatment session and therapy consisted of conventional therapy only with the affected upper extremity whereas experimental group also received 45 minutes of treatment session and therapy consisted of conventional therapy along with mirror therapy for three days/week. Outcome measures used were Fugl-meyer assessment and Functional independent measure. Results: Comparison of the changes in the Fugl-meyer assessment and Functional independent measure from baseline to six weeks between control and experimental group, revealed that significant improvement were in experimental group which was (p<0.05). Conclusion: Combination of conventional and mirror therapy is an effective method on restoring upper limb motor function among hemiplegic patients. Bangladesh Journal of Medical Science Vol.19(2) 2020 p.208-213